PENGEMBANGAN MEDIA INTERAKTIF MENGGUNAKAN ARTICULATE STORYLINE 3 PADA MATERI KONSEP ASAM BASA - Pratiwi, Ika Bella; Hasby; Ahmad Fauzi Syahputra Yani (Universitas Samudra, 2025)
This research is an innovation in learning media development, by creating interactive media based on Articulate Storyline 3 on acid-base concept. The method used is Research and Development (R&D) with the ADDIE development model. Data were collected through validation sheets filled out by material and media experts, as well as response questionnaires involving teachers and students. The trial was conducted on 28 students of class XI IPA 2 at SMAN 2 Langsa. The validation results showed a score of 0.87 from the material expert and 0.93 from the media expert. In addition, the practicality results based on response questionnaires from teachers and students reached 90.4%. Thus, the interactive media that has been developed is declared feasible and practical to be used in learning acid-base concepts.